Simultaneous Determination of Ten Active Compounds in the Whole Plant of Sarcandra glabra and its Related Traditional Chinese Medicinal Preparations by Ultra High Performance Liquid Chromatography - Li, X.; Yang, L.; Zeng, X.; Deng, Y.H.; Zhang, Y.F.; Wu, B. (Asian Journal of Chemistry, 2011)
A simple, senstive and specific ultra high performance liquid chromatography (UPLC) was established for the simultaneous determination of ten active compounds in Sarcandra glabra and its preparations e.g., Qingrexiaoyanning capsule, Zhongjiefeng tablet, Xiekang capsule, Jinsulan liniment and Zhongjiefeng injection. The analysis was performed on acquity UPLC system with acquity UPLC BEH C18 column (50 mm × 2.1 mm I.D., 1.7 μm) and gradient elution of acetonitrile and water containing 0.1 % formic acid, and all ten major compounds achieved complete separation. Results indicate that the developed UPLC assay can be successfully utilized as a quality method for simultaneous determination of ten representative compounds in Sarcandra glabra and its related preparations.